2019
DOI: 10.1016/j.ptsp.2018.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of shoulder injury in sub-elite level water polo players

Abstract: Investigate the patterns and circumstances of shoulder injury, in both male and female sub-elite water polo players, through evaluating the injury incidence, mechanism and subsequent training time lost. Design: Retrospective cohort. Setting: Sports institute. Participants: 80 sub-elite water polo players Main Outcome Measures: Total injury number and incidence, mechanism of injury, lost training time and time from injury onset to seeking treatment.Results: For the athlete self-report data set (2009-2013), 218 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 18 publications
1
30
0
2
Order By: Relevance
“…In the present Information were obtained from 344 athletes from joint injury group, 297 athletes from muscle injury group and 188 athletes from tendinopathy group. f Information were obtained from 344 athletes from joint injury group and 299 athletes from muscle injury group study, the prevalence of shoulder tendinopathy was in agreement with that observed by Hams and colleagues in Australian water polo athletes [29].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In the present Information were obtained from 344 athletes from joint injury group, 297 athletes from muscle injury group and 188 athletes from tendinopathy group. f Information were obtained from 344 athletes from joint injury group and 299 athletes from muscle injury group study, the prevalence of shoulder tendinopathy was in agreement with that observed by Hams and colleagues in Australian water polo athletes [29].…”
Section: Discussionsupporting
confidence: 79%
“…The prevalence of injuries in the ankle and knee joint and posterior thigh muscle found in our study can be explained by the dynamics of spin acceleration and jumping and landing tasks with only one foot [26,28]. Water polo is a team and contact sport with dynamic movements without the contribution of a solid base of support, which may cause micro-tears of the musculoskeletal structures, mainly the shoulder tendon, due to repetitive throwing movements [29][30][31]. In the present Information were obtained from 344 athletes from joint injury group, 297 athletes from muscle injury group and 188 athletes from tendinopathy group.…”
Section: Discussionmentioning
confidence: 57%
“…The GIRD values in these athletes are lower when compared to other modalities of overhead athletes 15 . In water polo, few studies have shown that GIRD is typical in this athlete population 3 . However, there is no significant correlation with pain/injuries 16 .…”
Section: Introductionmentioning
confidence: 98%
“…The body part most affected by injuries in competitive water polo players is the shoulder [1][2][3] , due to the nature of the sporting movement that involves swimming, throwing, and defending. The leading cause of these injuries is shoulder overuse 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation